2011
DOI: 10.1097/bpo.0b013e31821ffa82
|View full text |Cite
|
Sign up to set email alerts
|

Intercalary Segmental Reconstruction of Long Bones After Malignant Bone Tumor Resection Using Primary Methyl Methacrylate Cement Spacer Interposition and Secondary Bone Grafting

Abstract: IV (case series).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…Eleven patients who had reconstruction of the lower limb achieved weightbearing 4.1 months after the second stage of the procedure despite numerous complications such as nonunion and fracture [28]. The differences between that study [28] and our series in terms of complications can be explained by the high stability of our reconstruction technique with the use of a fibula support inside the membrane and a locking plate outside the membrane.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…Eleven patients who had reconstruction of the lower limb achieved weightbearing 4.1 months after the second stage of the procedure despite numerous complications such as nonunion and fracture [28]. The differences between that study [28] and our series in terms of complications can be explained by the high stability of our reconstruction technique with the use of a fibula support inside the membrane and a locking plate outside the membrane.…”
Section: Discussionmentioning
confidence: 51%
“…5) [26]. However, although the series reported by Masquelet et al [23] was large, the patients had only short-term followup, and other authors have suggested that nonunions and resorption of these grafts might occur [2,28]. We therefore sought to evaluate our early experience with the technique, specifically with respect to complications, bone healing, and functional outcomes at a minimum of 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations